PENGARUH TINGKAT KEPATUHAN WAJIB PAJAK ORANG PRIBADI TERHADAP PENERIMAAN PAJAK PENGHASILAN ORANG PRIBADI PADA KPP PRATAMA CIBINONG - Simamora, Patar; Suryaman, Deni (Universitas Pakuan, 2015)
ABSTRACTTax is one source of state revenue is used to finance the household of the State and individual taxpayerswho have responsible as a taxpayer who will increase the number of admissions personal income tax, butit does not increase the acceptance of personal income tax, when in reality the level of complianceindividual taxpayers still perceived remains low during this time. The goals to be achieved is to determinethe Effect of Individual Taxpayer Compliance on the Personal Income Tax Revenue on KPP PratamaCibinong. The method I use is descriptive analysis method which defines Effect of Individual TaxpayerCompliance to the Personal Income Tax Revenue on KPP Pratama Cibinong. Based on the research thathas been done, the writer can conclude that the level of the individual taxpayer Kepatuihan effect onPersonal Income Tax Revenue In KPP Pratama Cibinong.Keywords: Level of Compliance, TIN Registered, submission of tax returns, Payment of Tax, Tax ReceiptsOP.